Nek2 activation of Kif24 ensures cilium disassembly during the cell cycle - Kim, Sehyun (Nat Commun, 2015)
Many proteins are known to promote ciliogenesis, but mechanisms that promote primary cilia disassembly before mitosis are largely unknown. Here we identify a mechanism that favours cilium disassembly and maintains the disassembled state. We show that co-localization of the S/G2 phase kinase, Nek2 and Kif24 triggers Kif24 phosphorylation, inhibiting cilia formation. We show that Kif24, a microtubule depolymerizing kinesin, is phosphorylated by Nek2, which stimulates its activity and prevents the outgrowth of cilia in proliferating cells, independent of Aurora A and HDAC6. Our data also suggest that cilium assembly and disassembly are in dynamic equilibrium, but Nek2 and Kif24 can shift the balance toward disassembly. Further, Nek2 and Kif24 are overexpressed in breast cancer cells, and ablation of these proteins restores ciliation in these cells, thereby reducing proliferation. Thus, Kif24 is a physiological substrate of Nek2, which regulates cilia disassembly through a concerted mechanism involving Kif24-mediated microtubule depolymerization.